The Influence of Brand Experience, Brand Engagement, and E-WOM on Brand Equity of Lenovo Laptop Products - Rizky Oktaviani Isba; Kussudyarsana (Faculty of Economics and Business, University of Pancasakti Tegal, 2024)
This study aimed to analyze the influence of brand experience, brand engagement, and electronic word of mouth (e-WOM) on brand equity for Lenovo laptop products. The research employed a quantitative method with purposive sampling, collecting data from 160 Lenovo users in Indonesia through structured questionnaires. Data analysis utilized validity and reliability tests, classical assumption tests, and multiple linear regression. The findings revealed that brand experience, brand engagement, and e-WOM had positive and significant effects on brand equity. Among these, e-WOM had the strongest impact, indicating the critical role of consumer communication in enhancing brand perception. Although the research successfully highlights important factors influencing brand equity, it is limited by the demographic concentration of young respondents and the reliance on self-reported data. This study contributes originality by integrating brand experience, engagement, and e-WOM in a single model within the Indonesian technology market context. It offers practical value for marketers seeking to strengthen brand positioning in increasingly digitalized markets